2017
DOI: 10.1111/1462-2920.13729
|View full text |Cite
|
Sign up to set email alerts
|

A novel, highly conserved metallothionein family in basidiomycete fungi and characterization of two representativeSlMTaandSlMTbgenes in the ectomycorrhizal fungusSuillus luteus

Abstract: The basidiomycete Suillus luteus is an important member of the ectomycorrhizal community that thrives in heavy metal polluted soils covered with pioneer pine forests. This study aimed to identify potential heavy metal chelators in S. luteus. Two metallothionein (MT) coding genes, SlMTa and SlMTb, were identified. When heterologously expressed in yeast, both SlMTa and SlMTb can rescue the Cu sensitive mutant from Cu toxicity. In S. luteus, transcription of both SlMTa and SlMTb is induced by Cu but not Cd or Zn.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 61 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…Expression levels of eight genes ( MnSOD, HSP70, ZRT1, ZnT1, ZnT2, GST, GSS, MTa ) and three reference genes ( GR975621, AM085168, AM085296 ) were measured. Primer sequences (Table S2) were taken from Coninx et al , (2017), Muller et al (2007), Nguyen et al (2017), Ruytinx et al (2011, 2016, 2017), or newly designed using the Primer3 program (Rozen & Skaletsky, 2000). Real-time PCR was performed in an optical 96-well plate with an ABI PRISM 7500 sequence detection system (Applied Biosystems) and fast cycling conditions (20s at 95°C, 40 cycles of 3s at 95°C and 30s at 60°C) according to Ruytinx et al , 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression levels of eight genes ( MnSOD, HSP70, ZRT1, ZnT1, ZnT2, GST, GSS, MTa ) and three reference genes ( GR975621, AM085168, AM085296 ) were measured. Primer sequences (Table S2) were taken from Coninx et al , (2017), Muller et al (2007), Nguyen et al (2017), Ruytinx et al (2011, 2016, 2017), or newly designed using the Primer3 program (Rozen & Skaletsky, 2000). Real-time PCR was performed in an optical 96-well plate with an ABI PRISM 7500 sequence detection system (Applied Biosystems) and fast cycling conditions (20s at 95°C, 40 cycles of 3s at 95°C and 30s at 60°C) according to Ruytinx et al , 2017.…”
Section: Methodsmentioning
confidence: 99%
“…The gene repertoire for all kinds of metal detoxification pathways is present in ectomycorrhizal fungi (Bolchi et al , 2011). In S. luteus , different Zn transporters with a function in cellular Zn uptake and distribution were characterized (Coninx et al, 2017; Ruytinx et al, 2017) and genes encoding additional proteins putatively involved in homeostasis, detoxification and damage repair were identified (Muller et al, 2007, Ruytinx et al, 2011, Nguyen et al, 2017). In the current study, we hypothesize contrasting Zn tolerance phenotypes in S. luteus to be due to alterations in general mechanisms of Zn homeostasis, detoxification or damage repair.…”
Section: Introductionmentioning
confidence: 99%
“…Several MT genes were characterized, and their expression levels were assessed in fungal cells in response to HMs. In S. luteus , SlMTa and SlMTb function as chelators for Cu 2+ and the transcript abundance of both genes is increased by exposure to excess Cu 2+ (Nguyen et al, ). Similarly, the transcriptional levels of the MT genes from Laccaria bicolor (Maire) P.D.…”
Section: Physiological and Molecular Mechanisms Of Hm Accumulation Inmentioning
confidence: 99%
“…Five cysteine‐rich proteins were found using metagenomics analysis, and were designated as a new, formerly undescribed, MT family with distinct sequences and features . A novel fungal MT family, which includes SlMTa and SlMTb , of the basidiomycete Suillus luteus and showing specific number and distribution of cysteine residues was reported . With a combination of protein heterogeneity and fewer amino acids, MTs are generally difficult to identify and classify just by using sequence similarity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…MTs are multiregulated proteins in fungi and yeasts, and a variety of abiotic stresses may induce different expression in organisms. In the ectomycorrhizal fungus Suillus luteus , transcription of the MT genes SlMTa and SlMTb was induced when the fungus was exposed to sublethal concentrations of Cu, but not after exposure to Cd and Zn . Reddy et al exposed the ectomycorrhizal fungus Laccaria bicolor to metal stress conditions and found that while the expression levels of two MT genes, LbMT1 and LbMT2 , increased under copper stress, only LbMT1 responded to elevated Cd levels in the range of 25–100 mM and neither responded to Zn.…”
Section: Introductionmentioning
confidence: 99%